Chromium Removal From Strong Base Anion Exchange Waste Brines. Issue 4 (1st April 2016) - Li, Xue; Green, Peter G.; Seidel, Chad; Gorman, Craig; Darby, Jeannie L.
Abstract : Regeneration of strong base anion (SBA) exchange resin produces concentrated and hazardous brine. In this research, one alternative regenerant and two brine treatment options were investigated to reduce the hazardous characteristics of the brine. These options included replacing sodium chloride with sodium bicarbonate as the regenerant, using ferrous sulfate (FeSO4 ) to reduce/coagulate hexavalent chromium (CrVI) in the brine, and applying weak base anion (WBA) exchange resin and chemical reductive media (CRM) to adsorb/reduce CrVI. It was found that bicarbonate was as effective as chloride in regenerating chromium‐saturated resins, and the affinity of the bicarbonate‐form resin for chromium was similar to that of the chloride‐form resin. It was observed that FeSO4 applied at doses close to the stoichiometric ratio achieved almost complete removal of total chromium from the SBA brine. In column tests, two CRM exhibited more than 20 times greater removal capacity for total chromium than did the WBA exchange resins.